“Architects of Their Own Brain.” Social Impact of an Intervention Study for the Prevention of Gender-Based Violence in Adolescence - Racionero-Plaza, Sandra; Ugalde, Leire; Merodio, Guiomar; Gutiérrez-Fernández, Nerea (Frontiers in Psychology, 2020)
Research in psychology has evidenced both the important prevalence of gender-based violence among youth worldwide, and the negative impacts that such violence has on the victims’ mental and physical health. Neuroscience has proven that violent intimate relationships harm the brain, while very simple social experiences can change brain architecture in positive directions. Also, interventions which have demonstrated successful in preventing and responding to gender violence in adolescence have been informed by psychology. This article reviews the social impact of psychology in the field of teen gender violence to later report the potential social impact achieved by an intervention study consisting of seven interventions framed by the research line on preventive socialization of gender violence. The program was addressed to 15 and 16-year-old adolescents and focused on supporting free reconstruction of mental and affective models of attractiveness via critical analysis of the dominant coercive discourse, which links attraction to violence. The communicative methodology involved working with an Advisory Committee since the beginning of the study, as well as continuous dialogue between the researchers and the participants, which was used to refine subsequent interventions. The results show that the program contributed to raise participants’ critical consciousness regarding the dominant coercive discourse in their life, provided the participant subjects with cognitive tools to better understand theirs and others’ sexual-affective thinking, emotions and behaviors, in favor of rejecting violence, and the interventions supported modifying the sexual preferences of female adolescents. Importantly, the findings also indicate that the interventions aided some participants’ use of the knowledge gained in the project to help their friends and communities in reflecting upon coercive patterns of sexual attraction, about the quality of their intimate relationships and their different effect on health. Some individuals reported leaving toxic relationships afterwards. This intervention research illustrates Santiago Ramón y Cajal’s metaphor employed to explain plasticity, as every person, if s/he decides it, can be architect of her or his own brain. With evidence-based cognitive tools at the reach of every adolescent, and upon individual free choice for transformation, a new sexual-affective socialization free from violence is possible.